(untitled) (American Journal of Islam and Society, 2004)
The current surge of attention and sensitivity to Islam in western academia and popular culture often boils down to the question of Islam’s compatibility – or lack thereof – with modernity. The issue is by no means a simple one, and is further complicated by the fact that both “Islam” and “modernity” are made to carry a heavy load of multiple definitions that are also susceptible to ideological uses and abuses. Such influential American commentators as Francis Fukuyama, Daniel Pipes, and Bernard Lewis have been unanimous in their diagnosis that while Judaism and Christianity have come to terms with modernity, Islam has so far failed to take that necessary and crucial step. In the larger context of modern Muslim history, however, the question is almost two centuries old; it was repeatedly grappled with in the past and continues to occupy a prominent place in the Muslim consciousness. Sheila McDonough’s new book on Muhammad Iqbal (1877- 1938) can be approached with reference to this particular discourse, for the question of Islam and modernity was perhaps the most important factor that motivated and shaped Iqbal’s creative output – a body of ideas whose revelance has tremendously increased in the six decades since his death. While Iqbal’s poetic and intellectual genius has been greatly celebrated and widely acclaimed, both within the Indian subcontinent and abroad, it can be safely contended that his true potential as the twentieth century’s most important post-critical Muslim philosopher is yet to be discovered. In view of his work’s creativity, depth, and visionary reach, the number and quality of English-language studies on Iqbal’s thought leave much to be desired. In this context, McDonough has done a remarkable service by making the intellectual and imaginal contours of Iqbal’s consciousness accessible to a new generation of Muslim and non-Muslims readers, many of whom have been recently sensitized to the question of Islam’s relationship with modernity. Mixing her serious erudition with a loving sensitivity and an almost artistic gift for discerning interconnections, McDonough skillfully blends together the accounts of the vicissitudes of Iqbal’s personal life, his turbulent socio-historical context, and his sometimes shocking ideas to paint a colorful picture of his life, times, vision, and struggle. The Flame of Sinai is sure to become a classic, alongside a similar work by another Western admirer of Iqbal, namely, the late Annemarie Schimmel’s book Gabriel’s Wing. Incidentally, both of these charming titles come from Iqbal’s own symbolic imagination ...